Domniemane i rzeczywiste kontakty prominentów nazistowskich z polskością przed 1933 rokiem - Kapica, Wojciech (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The article is an attempt to examine the contacts of prominent Nazis with Polishness before 1933. The author looks at these contacts with regard to the place of birth, living in a given place until 1918, living in a given place in the inter-war period 1918–1933, participation in the First World War in Poland, participation in Polish-German fighting in 1918–1921, having a Polish-sounding name and impact of all these factors on the period of the Second World War German occupation of Poland.
Keywords: narodowy socjalizm; Trzecia Rzesza; walki polsko-niemieckie; mniejszość niemiecka w Polsce; okupacja niemiecka w Polsce